Doubling off-axis electron cyclotron current drive efficiency via velocity space engineering. (1st May 2022) - Chen, Xi; Petty, C.C.; Lohr, J.; Su, D.; Prater, R.; Cengher, M.; Austin, M.; Holcomb, C.; Lao, L.; Pinsker, R.I.; Victor, B.; Zeng, L.
Abstract: For the first time, experiments on the DIII-D tokamak have demonstrated electron cyclotron current drive with more than double the conventional efficiency by tailoring the wave–particle interactions in velocity space using a novel 'top launch' geometry. Steering the EC waves to propagate nearly parallel to the resonance drives current more efficiently by (1) selective damping on electrons with higher parallel velocity v ||, and (2) longer absorption path to compensate for inherently weaker absorption at higher v ||. Experiments using a fixed-injection top launch system find an optimal velocity space interaction for maximum current drive efficiency at ρ ∼ 0.5 where the ease of drawing out a high v || electron tail is balanced by sufficient absorption.